2015
DOI: 10.1038/cddis.2015.79
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adipocytes derived from fibro/adipogenic progenitors resident in human skeletal muscle

Abstract: A population of fibro/adipogenic but non-myogenic progenitors located between skeletal muscle fibers was recently discovered. The aim of this study was to determine the extent to which these progenitors differentiate into fully functional adipocytes. The characterization of muscle progenitor-derived adipocytes is a central issue in understanding muscle homeostasis. They are considered as being the cellular origin of intermuscular adipose tissue that develops in several pathophysiological situations. Here fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 50 publications
7
105
0
1
Order By: Relevance
“…Analysing both polyclonal and monoclonal cell cultures, we could not identify any MP subpopulation with adipogenic potential. Our results further support previous work showing that MPs are committed to the myogenic fate30, 31, 49, 51 and that FAPs are the adipocyte precursor population residing in murine30, 31, 32, 52 and human24, 51, 53, 54 adult skeletal muscle. Although we cannot reject the hypothesis that a small subpopulation of satellite cells could form brown adipocytes—as shown by Yin et al 27.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Analysing both polyclonal and monoclonal cell cultures, we could not identify any MP subpopulation with adipogenic potential. Our results further support previous work showing that MPs are committed to the myogenic fate30, 31, 49, 51 and that FAPs are the adipocyte precursor population residing in murine30, 31, 32, 52 and human24, 51, 53, 54 adult skeletal muscle. Although we cannot reject the hypothesis that a small subpopulation of satellite cells could form brown adipocytes—as shown by Yin et al 27.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown adipogenic potential for CD56 − /CD15 +, 24, 61 CD56 − /PDGFRα +, 54 or CD56 − /CD15 + /PDGFRα + 51 progenitors isolated from human skeletal muscle. These progenitors have been described to give rise to bona fide white adipocytes that are insensitive to insulin‐induced glucose uptake compared with adipocytes derived from progenitors isolated from subcutanous adipose tissue 51. In contrast, Uezumi et al 54.…”
Section: Discussionmentioning
confidence: 94%
“…A subset of progenitor cells in skeletal muscles, referred to as FAPs, are characterized by the expression of cell surface marker PDGFRA and exclusion of other cell types known to express PDGFRA, such as bone marrow-derived progenitors 6, 8, 24, 25 . In the heart presence and characteristics of FAPs and the subset that differentiate to adipocytes are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Adipsin is a mature adipocyte marker. 33 qRT-PCR analysis of adipogenic markers PPARc and adipsin revealed that there was no significant difference in PPARc expression across the frozen-thawed samples ( p > 0.05) (Fig. 4C).…”
Section: Differentiationmentioning
confidence: 86%